A companion to biological anthropology - Larsen, Clark Spencer (Wiley-Blackwell companions to anthropology, 2023)
"The fundamental subject matter of biological (formerly physical) anthropology focuses on human origins and human variation. Such interests date back to antiquity, but systematic observations and publications began with the 18th century Natural Philosophers of the Enlightenment, such as George-Louis Leclerk, Comte de Buffon (1707-1788) and James Burnett, Lord Monboddo (1714-1799)"--